How ETFs Amplify the Global Financial Cycle in Emerging Markets - Converse, Nathan (2023)
We study how the growth of exchange-traded funds (ETFs) affects the sensitivity ofinternational capital flows to the global financial cycle. Using comprehensive fund-leveldata on investor flows, we show that their sensitivity to global financial conditions for equity(bond) ETFs is 2.5 (2.25) times higher than for equity (bond) mutual funds. This highersensitivity can be directly linked to ETFs underlying shorter-trading-horizon clientele thattrades more often in response to shocks. Using country-level data, we find that where ETFshold a larger share of financial assets, equity inflows and prices become more sensitive toglobal risk.